The study on material surface on the effect of the Low-Intensity Pulsed Ultrasound (LIPUS) for Osseointegration of the Hydroxyapatite coating dental implant - Masanori Kobayashi (Journal of Dental Problems and Solutions - Peertechz Publications, 2020)
Excellent osseointegration of biomaterial is very important for the stability of dental implants in clinical field. Much has been learned about this concept and significant improvements on the design and surface modification of implants have been done in the implant dentistry.  Recently, some clinical studies have also reported that low-intensity pulsed ultrasound Irradiation (LIPUS) might enhance the osseointegration (bone-bonding) by means of X-ray radiographic evaluation.  We have already reported that the LIPUS could accelerate the bone-like hydroxyapatite precipitation on the bioactive material surface, which corresponds to osseointgration function. In this review, the mechanism of osseointegration enhanced by LIPUS was presented by the data of our in vitro and in vivo study on hydroxyapatite surface using a Scanning electron microscope and X-ray diffraction analysis. This review suggested that the formation of bone-like apatite on material surface is very important for rapid and firm osseointegration success, which might depend on the initial epitaxial nucleation and crystal growth of apatite on the surface, and LIPUS could activate this crystallization process.